Denimalz Mascot Plush Design: A Study on Cute Character Design Principles - Laurencia, Jessica (ULTIMART Jurnal Komunikasi Visual, 2025)
This research explores the role of visual design in enhancing the appeal of character mascots, especially cute characters. Cute mascots are often more favored by audiences, as seen in the evolution of characters like Mickey Mouse, whose design has become increasingly childlike, in line with the principles of Kindchenschema. While previous existing study has explored what visual elements make mascots appear cute, most studies examined different types of mascots. This research focuses on a single mascot series that has undergone several subtle design changes over the years, Denimalz, a mascot of South Korean Pop Rock Band Day6. The research aims to identify which visual features make a character look cuter to audiences by using a mixed-methods approach. Data were collected through a survey of 129 participants including both fans and non-fans, along with open-ended questions, visual analysis of Denimalz plush versions, and a comparison with existing design theories. The findings show that facial expression and proportion or ratio are the two dominant features that determine cuteness. Future studies are recommended to explore cultural differences in cuteness perception, particularly how audiences from different regions interpret the same design elements. Keywords: cute character design, mascot, kindchenschema, Denimalz